Comparison of the effects of green betel leaf (piper betle ) and red betel leaf (piper crocatum) extracts on the growth of staphylococcus aureus bacteria - Tenia Alfitri (International Journal of Nursing and Midwifery Research, 2022)
Betel leaf is well known in Indonesia as a therapeutic herbal. Betel leaf extract contains phenol, euganol and chavicol which can inhibit the growth of bacteria such as Staphylococcus aureus. Phenol can denature the cell protein of bacteria, euganol as bacteriostatic, and chavicol has a bactericidal effect five times more than other phenol derivatives. Red Betel leaf also has some good effect on our body. Research on the effect of red betel leaf is not as much as the effect of betel leaf extract. Because two kinds of piper leaf have some effect as antibacterial, so the purpose of this study is to know the comparison of the antibacterial potency of ethanol extract of red betel vine (Piper crocatum) and beter leaf extract toward the growth of Staphylococcus Aureus. This research use diffusion disk method and with concentration 250 mg/ml, 500mg/ml, 750mg/ml, and 1000mg/ml. The result from this research is that the effect of betel leaf extract at concentrations of 250mg/ml and 500mg/ml is lower than the effect of red betel leaf extract, but at high concentrations of 750mg/ml and 1000mg/ml the effect of betel leaf extract is higher than red betel leaf extract.